Community Foundations : A Tool for Preservation of Cultural Heritage - World Bank (Washington, DC, 2012)
This note emphasizes that Community Foundations present a practical instrument to supplement larger cultural heritage projects and to support the preservation and use of cultural heritage applying community driven development (CDD) approaches. This is relevant especially since while existing World Bank instruments have proven suitable for financing infrastructure projects, including projects that preserve material culture such as historical buildings, structures and landscapes, it is often much more difficult to support preservation and use of small and intangible cultural heritage.